2014
DOI: 10.1136/bmjopen-2014-005886
|View full text |Cite
|
Sign up to set email alerts
|

HIV virological failure and drug resistance among injecting drug users receiving first-line ART in China

Abstract: ObjectiveTo explore HIV virological failure and drug resistance among injecting drug users (IDUs) receiving first-line antiretroviral treatment (ART) in China.DesignA series of cross-sectional surveys from 2003 to 2012 from the Chinese National HIV Drug Resistance (HIVDR) Surveillance and Monitoring Network.SettingChina.ParticipantsData were analysed by the Chinese National (HIVDR) Surveillance and Monitoring Network from 2003 to 2012. Demographic, ART and laboratory data (CD4+ cell count, viral load and drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
8
29
2
Order By: Relevance
“…The first factor reflected that adherence was a direct factor causing HIVDR, with 21(2.7%) patients having reported to have lower than 90% of drug intake in the past month. Similar findings had been reported in our previous studies in China [19, 27, 30], where poor adherence clearly leads to the occurrence of HIVDR. Good adherence can suppress plasma HIV RNA and utilize the optimum effectiveness of the ART therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The first factor reflected that adherence was a direct factor causing HIVDR, with 21(2.7%) patients having reported to have lower than 90% of drug intake in the past month. Similar findings had been reported in our previous studies in China [19, 27, 30], where poor adherence clearly leads to the occurrence of HIVDR. Good adherence can suppress plasma HIV RNA and utilize the optimum effectiveness of the ART therapy.…”
Section: Discussionsupporting
confidence: 92%
“…A combination of strategies is required to combat drug resistance. New medicines that can more robustly cope with drug resistance mutants are needed, especially for those with common mutations such as K103N and M184I/ V [19, 26, 27]. M184I/V confers resistance to lamivudine, which is often the first mutation to develop in patients receiving partially suppressive triple combination therapy including lamivudine [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were small numbers of patients who were injection drug users in our study, they have a higher risk of developing unfavorable outcomes similar to what has been shown elsewhere [21]. …”
Section: Discussionsupporting
confidence: 82%
“…49 In the IDU population, the data from the Chinese National (HIVDR) Surveillance and Monitoring Network showed that 20.8% of individuals undertaking first line drugs experienced virological failure. 50 Here we found that a low level of drug-resistant strains was found in Liangshan, suggesting that the ART program in Liangshan is functioning well.…”
Section: Figmentioning
confidence: 58%